Investigating the Financial Performance of Universities of Medical Science and Health Services in Iran, Using Data Envelopment Analysis. - Amir Ashkan Nasiripour; Abbas Toloie-Ashlaghy; Seyed Jamaleddin Ta-Bibi; Mohammad Reza Maleki; Hassan Abolghasem Gorji (Tehran University of Medical Sciences, 2014)
Universities of Medical Science and Health Services (UMSHSs) are among the main organizations in Iran's health-care section. Improving their efficiency in financial resource management through creating an appropri-ate coordination between consumption and resources is strategically vital. Investigating the financial performance as well as ranking the Iranian UMSHSs is the research objective.The study is of descriptive and applied type. The study population includes the UMSHSs of Iran (n=42) among which 24 UMSHSs are selected. DEA is used with the aim to model and assess the financial performance in-cluding 4 inputs and 3 outputs. Also, linear regression is applied to determine the effectiveness of the applied indices as well as the level of the financial performance. Data are obtained from the Budgeting Center in the Ministry of Health and Medical Education, during 2010 mainly through forms designed based on the available balance sheets.The average score of financial performance assessment for UMSHSs based on the DEA of input-oriented data is 0.74, assuming a constant scale of DEA-CRS. Thus, approximately 25% of the studied UMSHSs have maxi-mum relative performance and totally, there is about a 30% capacity to increase the financial performance in these UMSHSs.Most Iranian UMSHSs do not have high financial performance. This can be due to problems in financial resource management especially in asset combining. Therefore, compilation and execution of a comprehensive pro-gram for organizational change and agility with the aim to create a kind of optimized combination of resources and assets is strongly recommended.